(untitled) (Uzbek Scholar Journal, 2025)
This study investigates the impact of single parenthood on the academic achievement of tertiary education students at the University of Port Harcourt, Rivers State, Nigeria. Using a structured questionnaire administered to 385 students from single-parent households, the study explores the influence of socio-economic status, parental involvement, emotional support, and common challenges faced by these students. Findings reveal that higher parental income, educational attainment, and stable occupations significantly correlate with improved academic performance. Emotional support emerged as the strongest predictor, tripling the likelihood of academic success, followed closely by active parental involvement. Major challenges identified include financial strain, time management issues, emotional burden, and reduced parental involvement. The study recommends enhanced emotional support systems, institutional interventions to promote academic inclusion, and targeted support services to mitigate the challenges faced by students from single-parent households. These findings underscore the critical need for holistic academic support frameworks that consider family structure and socio-emotional dynamics.